MIGRATION AND THE MAKING OF IRELAND - FANNING, BRYAN (INDIANA UNIV PRESS, 2021)
Engaging and eloquent, Migration and the Making of Ireland provides long overdue consideration to those who made new lives in Ireland even as they made Ireland new.